Supervision and Law Enforcement of Business Competition in the Digital Industry (Case Study of Predatory Pricing Practices in the TikTok Shop) - Nurmal, Ireina Rahayanti (JURNAL AKTA, 2024)
The one of problems that should be resolved is predatory pricing that occurs in the digital industry which is always in the spotlight in Indonesian society. KPPU is an independent institution established based on Law No. 5 of 1999 concerning the prohibition of monopoly and unfair business competition which has the authority to supervise and enforce legal business competition practices. The KPPU was asked to be more proactive in investigating predatory pricing in e-commerce, one of which is TikTok Shop. The entry of imported goods in the TikTok Shop which are sold at prices much lower than the cost of local products and flash sale platforms is troubling MSME business actors because it can kill the MSME market which will be the focus of the discussion in this research. The national economic system, which includes elements of business competition, has not been built under the standards of prosperous and fair business competition. Regulations governing business competition in the digital industry must also be carefully considered. KPPU still faces big problems with predatory pricing. Because the market is different from conventional industries, current rules may need to be adjusted to stop anti-competitive practices. E-commerce regulations are still lacking to ensure law enforcement against false pricing practices. The TikTok Shop case is a valuable lesson for authorities and other stakeholders in facing new challenges emerging in the digital industry. Competitors affected by this practice may experience significant financial losses, while customers may benefit in the short term, but in the long term they are at risk.